PENGARUH MUTU PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RSUD KESEHATAN KERJA - Riza Masitoh Hasifa; Ai Susi Susanti (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine the influence of the quality of health services on the satisfaction of inpatients at the Occupational Health Hospital of West Java Province. The research method used is a quantitative method with a descriptive approach. Data collection techniques include distributing questionnaires and conducting literature studies. The total population is 2.500 patients per month. The sampling technique uses random sampling with a total sample size of 50 people. The data analysis techniques used are validity tests, reliability tests, and Spearman rank correlation tests. The research results show that the Spearman rank correlation coefficient value is 0.65 in the interval 0.6–0.799, which is categorized as strong. So, it can be concluded that the quality of health services has a strong influence on the satisfaction of inpatients at the West Java Province Occupational Health Hospital.